Investigating follower felt trust from a social cognitive perspective. Issue 6 (2nd November 2019) - Zheng, Xiaotong; Hall, Rosalie J.; Schyns, Birgit
ABSTRACT: Previous organizational research on trust has focused more on subordinates' trust in their leaders than on their experience of felt trust from the leader, even though the latter is also an important component of trust relationships. Our paper addresses a recent call for more theoretical explanations of the mechanism through which followers' felt trust influences their in-role and extra-role performance. Based on social cognitive theory, we proposed that occupational self-efficacy (OSE) mediates the felt trust-performance relationship in workplace settings, and tested these relationships in two empirical studies. Study 1 was a cross-sectional pre-study ( N = 189) investigating only the mediating effects of OSE. For the main study, i.e., Study 2 ( N = 500), we collected data at three different measurement occasions to minimize response bias. Study 2 investigated the mediation of the felt trust-performance relationship not only by OSE, but also by an additional mediator variable (organization-based self-esteem) that had been identified in previous studies, in order to determine whether the OSE effects remained significant. In both studies, structural equation modelling results supported the proposed mediating effects of OSE on the three performance outcomes for the reliance component of felt trust, but not for the disclosure component of felt trust.